Spatiotemporal desynchronization in the propagation from meteorological to soil moisture drought in the Loess Plateau, China - Mingqiu Nie; Shengzhi Huang; Xin-Min Zeng; Jian Peng; Ganggang Bai (Journal of Hydrology: Regional Studies)
Study Region: The Loess Plateau (LP) of China Study Focus: Meteorological drought (MD) would propagate to soil moisture drought (SMD) with spatiotemporal desynchronization. The spatial desynchronization between them has frequently been ignored in previous studies due to limitation of identified droughts, which did not consider their 3-dimensional (3D, i.e. longitude, latitude and time) properties. This study presents a 3D perspective on the spatiotemporal desynchronization in the propagation from meteorological to soil moisture drought in the the Loess Plateau (LP) of China, using an improved drought matching method. Event Synchronization (ES) is extended to determine temporal linkage of the two types of droughts and spatial connection is tested using overlapping area. New Hydrological Insights for the Region: The results showed that: (1) the improved method is reasonable for identifying MDs that trigger SMDs, down to specific clusters; (2) 8 SMDs preceded MDs 1 month, while approximately 79 % of SMDs did not recover after the determination of MDs; (3) severity of MD is an impact factor on recovery lag, while antecedent soil moisture dominates onset lag with the relative importance of approximately 50 %; and (4) incompletely overlap in migration trajectory between the two types of droughts was mainly caused by temperature, followed by antecedent soil moisture and potential evapotranspiration, with relative importance of 55 %, 14 % and 12 %, respectively.